Pre-Wedding Photo Tradition Before the Ceremony: Analysis of Community Perceptions of the MUI Fatwa in North Sumatra - Nuryani, Siti; Akbar, Ali (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Pre-wedding photos have become part of popular culture carried out by brides-to-be, including in Pangkalan Village. However, there is a gap between the level of knowledge and public practice regarding Islamic law regarding these activities. In response to this phenomenon, the Indonesian Ulema Council (MUI) of North Sumatra Province issued Fatwa Number 03/KF/MUI-SU/IV/2011 which expressly prohibits pre-wedding photos before the marriage contract. This study aims to examine the perception of the people of Pangkalan Village towards the existence and implementation of the fatwa. This study uses an empirical method with a field research approach. Data collection was carried out through in-depth interviews with four couples who had taken pre-wedding photos, four religious leaders, and three mosque teenagers, and supported by observation and documentation. The results of the study showed that even though 75.61% of the public knew the MUI fatwa related to the ban, the practice of pre-wedding photos before the marriage contract was still prevalent, even with poses that were not in line with sharia values. Religious leaders fully support the fatwa and emphasize the importance of avoiding the practice of khalwat, ikhtilat, and physical touch that are prohibited in Islam. Meanwhile, mosque youth understand the rationale behind the fatwa, but face challenges in the form of social pressure and a desire to follow popular culture trends. Public perception of this fatwa is influenced by psychological factors, family environment, and local culture that develop in the community.